AB0188 Bone mineral density(bmd), serum calcidiol and knee osteoarthritis. (1st June 2001) - Hernán, M Bonilla; Aguado, P; Vacchiano, L; Martinez, E; Gamero, F; Berriatua, B; Mola, E Martín
Abstract : Background: Relationship between knee osteoarthritis (OA) and bone mass has brought a great interest. Serum calcidiol (CS) low level has been associated with a higher incidence and faster progression of OA in elderly women, but this relation has not been defined in young postmenopausal women. Objectives: The aim of the study was to determine the prevalence of knee OA in postmenopausal women and its relationship with bone density and CS levels. Methods: Prospective study realised in 89 women (mean age ± 5 years: range:47–66), all of them being diagnosed of natural menopause for at least 2 years before they were included in this study.(mean value of 7.9 ± 2). They were recruited at a rheumatology consultory. CS levels were determined by RIA, along the winter time because of the lest sunny hours during that period. Two critical values were established (<10, to calculate deficit prevalence. BMD was measured in lumbar spine and hip with DEXA (Hologic QDR 1000). Patients had to fulfil the WHO criteria to be diagnosed of osteoporosis. Knee OA was defined by a grade >2 in Kellgren-Lawrence radiologic scale. Prevalence difference was analysed by contingency tables. Results: A total of 58 women had OP while 31 had normal BMD. SC mean value was 13 ± 7.1 ng/ml and there were no significant differences comparing osteoporotic (OP) women with non-OP women. Knee OA prevalence was 65 (73%). In the OP. group and 80.6 in the non-OP. group. < 10 and 20 ng/ml CS deficit prevalence was 38.7% and 61.3% respectively women with knee OA and 39% and 78.3% respectively in women without knee OA. Conclusion: No inverse relationship was found between OP and knee OA in our group. CS deficit was not associated with a higher prevalence of knee OA in young postmenopausal women.